Autophagy as an innate immunity response against pathogens: a Tango dance - Aguilera, Milton Osmar (2023)
Intracellular infections as well as changes in the cell nutritional environmentare main events that trigger cellular stress responses. One crucial cellresponse to stress conditions is autophagy. During the last 30 years, severalscenarios involving autophagy induction or inhibition over the course of anintracellular invasion by pathogens have been uncovered. In this review, wewill present how this knowledge was gained by studying different microorganisms.We intend to discuss how the cell, via autophagy, tries to repel theseattacks with the objective of destroying the intruder, but also how some pathogenshave developed strategies to subvert this. These two fates can be comparedwith a Tango, a dance originated in Buenos Aires, Argentina, in whichthe partner dancers are in close connection. One of them is the leader,embracing and involving the partner, but the follower may respond escapingfrom the leader. This joint dance is indeed highly synchronized and controlled,perfectly reflecting the interaction between autophagy and microorganism.